Indicadores de exposição a fatores de risco e proteção à saúde do escolar: análise da Pesquisa Nacional de Saúde do Escolar (PeNSE), Brasil, 2012 - D'Elia, Camila Andreia (2016)
This thesis search to identify if schools and familiar characteristics are associates in students behavior. For that, exposure to risk factors and health protection indicators were created using the ‘Pesquisa Nacional de Saúde do Escolar (PeNSE) 2012’ from the Instituto Brasileiro de Geografia e Estatística (IBGE) data bases about 9° grade students. The twenty six indicators created approach the central themes of alimentation, health, violence, drug use, physical activities, being higher the healthier practices. The linear regression modeling were used as the data analysis. With the results analysis was possible to see that the familiar presence is essential for the student to have good school habits and healthier behaviors. The school also have a strong influence over the teenagers, so being important to students development.